MCX - An open-source framework for digital twins - Shahsavari Sajad; Immonen Eero; Rabah Mohammed; Haghbayan Mohammad-Hashem; Plosila Juha (United Kingdom, 2022)
This article describes ModelConductor-eXtended (MCX), which is an open-source software architecture for digital twins. The MCX framework facilitates co-execution of, and asynchronous data communication between, physical systems and their digital simulation models. MCX supports running FMUs (simulation models packaged according to the FMI specification) as well as machine learning models and customized models. We propose extensions to the previously published ModelConductor framework for higher performance and better scalability. The extensions include decoupling of the queue and the model computation module, utilization of a standard data transmission protocol and implementation of the facility to run time-consuming simulation models in a time synchronous manner. Additionally, three new validation case studies are presented. A performance evaluation shows that the extensions improve the average response time almost 4 times in three specific experiments. © ECMS Khalid Al-Begain, Mauro Iacono, Lelio Campanile, Andrzej Bargiela (Editors)
Proceedings of the 35th ECMS International Conference on Modelling and Simulation ECMS 2021